2023
DOI: 10.1146/annurev-fluid-120720-012204
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propulsion of Chemically Active Droplets

Abstract: Microscopic active droplets are able to swim autonomously in viscous flows. This puzzling feature stems from solute exchanges with the surrounding fluid via surface reactions or their spontaneous solubilization and from the interfacial flows resulting from these solutes’ gradients. Contrary to asymmetric active colloids, these isotropic droplets swim spontaneously by exploiting the nonlinear coupling of solute transport with self-generated Marangoni flows; such coupling is also responsible for secondary transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 111 publications
(195 reference statements)
4
57
0
Order By: Relevance
“…In the forced case, it has been incorrectly guessed in [10] that both the parallel and larger-magnitude anti-parallel states are stable, while the smaller-magnitude anti-parallel state is unstable (we have shown that the larger-magnitude anti-parallel state is transversely unstable). This claim has been referenced in a recent review on active drops [4] and in a recent axisymmetric numerical study [13]. We note that earlier weakly nonlinear analyses of forced active drops have concluded similarly to here that there is a stable parallel state and, in some cases, also two unstable anti-parallel states.…”
Section: Discussion and Numerical Demonstrationssupporting
confidence: 83%
See 2 more Smart Citations
“…In the forced case, it has been incorrectly guessed in [10] that both the parallel and larger-magnitude anti-parallel states are stable, while the smaller-magnitude anti-parallel state is unstable (we have shown that the larger-magnitude anti-parallel state is transversely unstable). This claim has been referenced in a recent review on active drops [4] and in a recent axisymmetric numerical study [13]. We note that earlier weakly nonlinear analyses of forced active drops have concluded similarly to here that there is a stable parallel state and, in some cases, also two unstable anti-parallel states.…”
Section: Discussion and Numerical Demonstrationssupporting
confidence: 83%
“…In contrast, the two anti-parallel steady states that exist above a critical Péclet value are both unstable, however the larger-magnitude anti-parallel state is stable under longitudinal perturbations. These findings agree with the heuristic 'relative-stability' predictions in [6,7] for a closely related active-drop model, but contradict the guess made in [10], later referenced in [4] and [13], that the larger-magnitude anti-parallel state is stable. Motivated by the instability of the anti-parallel states, we have studied the alignment dynamics of a spontaneously moving particle following the sudden application of a force.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Garnering inspiration from micro-organisms such as bacteria, algae, and spermatozoa, over the past couple of decades, researchers have devised artificial micro-swimmers . By utilizing an in-built mechanism which breaks the symmetry of their interactions with the surrounding medium, these artificial machines can perform autonomous motion analogous to the locomotion of microorganisms. On choosing appropriate chemistry, they typically self-generate either a chemical or a physical gradient in their vicinity, which drives their motion.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of non-biological self-propelled objects have been reported so far, e.g. Janus particles, [6][7][8][9] swimming droplets, [10][11][12][13][14][15] Quincke rollers, 16,17 and so on.…”
Section: Introductionmentioning
confidence: 99%